2021
DOI: 10.1007/s13399-021-01593-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ZnO/BaTiO3 adsorbent using Elaeagnus Angustifolia L. leaf extract and its evaluation for ciprofloxacin removal from aqueous solutions: an optimization study

Abstract: Especially, most papers have reported an increase in antibiotic resistance (AR) bacterial infections during the COVID-19 pandemic. Because of the outbreak of the SARS-CoV-2, antimicrobial resistance (AMR) should be controlled and reduced. Researchers have reported that the adsorption technique is an sufficient procedure for separating drugs such as antibiotics from aqueous solutions. The prepared of ZnO/BaTiO 3 nanocomposite using Elaeagnus Angustifolia L. leaf ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Previously, Zeynep Ciğeroğlu et al showed that ciprofloxacin antibiotics can be removed using ZnO/BaTiO 3 adsorbent [24]. Moreover, Zeynep Ciğeroğlu et al investigated that adsorption of tetracycline antibiotics can be done successfully from aqueous solutions using g-C 3 N 4 -ZnO-BaTiO 3 nanocomposite [25].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Zeynep Ciğeroğlu et al showed that ciprofloxacin antibiotics can be removed using ZnO/BaTiO 3 adsorbent [24]. Moreover, Zeynep Ciğeroğlu et al investigated that adsorption of tetracycline antibiotics can be done successfully from aqueous solutions using g-C 3 N 4 -ZnO-BaTiO 3 nanocomposite [25].…”
Section: Introductionmentioning
confidence: 99%